2018
DOI: 10.1620/tjem.244.219
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Prevalence of Hypertension and Blood Heavy Metals among Curry-Consumed Korean

Abstract: Curcuma longa is rich in curcumin and used to treat disease and in food as a spice, especially in curry dishes. The objective of the present study was to determine whether curry intake reduces blood levels of heavy metals and hypertension (HTN) using Korean National Health and Nutrition Examination Survey 2013 data (n = 1,350). Study subjects (n = 1,350) were divided into two groups: 1) a curry intake group (n = 603), members of which had consumed a curry dish more than once a month over the previous year, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Curcumin has been used not only for cooking but also in traditional medicine. It is known to be useful in various conditions, including cardiovascular health, cognitive function, and cancer treatment [ 36 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Curcumin has been used not only for cooking but also in traditional medicine. It is known to be useful in various conditions, including cardiovascular health, cognitive function, and cancer treatment [ 36 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eating curry lowered the risk of HTN development as well. We recommend conducting more painstakingly planned clinical trials due to the prevalence of HTN and the link between consuming curry and having lower blood levels of heavy metals [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study in mice showed that Cd administration with curcumin resulted in lower Cd levels in the blood and organs (liver, kidney) than in mice that received Cd only [74,75]. Regular consumption of curcumin was linked to lowered blood Cd and lowered risk of hypertension in a Korean study [76].…”
Section: Dietary Factors: Diet Qualitymentioning
confidence: 98%